Investigation of Financial Factors Affecting the Income of Share Certificates: An Example of Industrial Companies - Avcı, Tunahan (İşletme Araştırmaları Dergisi, 2021)
Purpose – This study attempted to determine the factors that affect the stock returns of industrial enterprises operating in the Istanbul Stock Exchnge. In addition, it was investigated whether the deteriorated economic indicators caused a change in investors' decisions in 2018. Design/methodology/approach – For this purpose, logistic regression analysis was performed for 2017- 2018 by using the financial ratios of 147 enterprises in the industrial sector. In the analysis, the stock return rate as a dependent variable, and return on equity, market value / book value, price / earnings, receivables turnover rate, asset turnover rate, inventory turnover rate, debt ratio, gross profit margin, and main operating profit margin ratios as independent variables were used. Findings – According to the results of the analysis, equity profitability ratio had a significant effect on stock returns in 2017, while the debt ratio and the main operating profit margin ratio had a significant effect in 2018. Discussion – When the results of both years were analyzed, it was seen that the financial factors on stock returns changed, thus it can be said that there was a change in the investors' decisions.